2016
DOI: 10.1177/1708538116682164
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach to splenic aneurysms

Abstract: Background Splenic artery aneurysm is a rare disease with possibly mortal complications. For years, the main method of treatment was excision of aneurysm with spleen. In recent years, several methods have been developed in order to salvage the spleen such endovascular techniques and aneurysmectomy. Objective The aim of our study was to determine the feasibility of laparoscopic aneurysmectomy with spleen salvage in cases of splenic artery aneurysm. Materials Analysis of prospectively gathered data containing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Alternative treatments include endovascular approaches with transcatheter embolization. 2,[7][8][9][10][11][12] REBOA is a minimally invasive technique using a balloon catheter to temporarily occlude the aorta in support of hemorrhage control. It provides proactive management of life-threatening, refractory hemorrhagic shock despite maximal conventional therapy and is potentially lifesaving with minimal complications when placed by trained providers.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative treatments include endovascular approaches with transcatheter embolization. 2,[7][8][9][10][11][12] REBOA is a minimally invasive technique using a balloon catheter to temporarily occlude the aorta in support of hemorrhage control. It provides proactive management of life-threatening, refractory hemorrhagic shock despite maximal conventional therapy and is potentially lifesaving with minimal complications when placed by trained providers.…”
Section: Discussionmentioning
confidence: 99%
“…SAA is defined as a segmental enlargement of the artery with a diameter of 10 mm. SAA rupture is a life-threatening condition with a mortality rate of up to 75% [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…In symptomatic patients, the most common complaints are epigastric or back pain. Some authors consider that all symptomatic patients, as well as patients with no symptoms, whose SAA is > 20 mm in diameter, should be surgically treated because of the possibility of rupture [12]. Particularly risky groups of patients are pregnant women, patients with portal hypertension, and patients in whom liver transplantation is planned [2,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their series of 11 patients with SAAs, Małczak et al reported successful aneurysmectomy with spleen preservation in seven patients with one patient undergoing partial splenectomy and two patients receiving intraoperative splenectomies. 18 Distal SAAs and those intimately associated with the splenic parenchyma are treated by splenectomy and occasionally distal pancreatectomy may be required for an embedded aneurysm. 19 More recently, laparoscopic aneurysmectomy with or without spleen preservation has been reported with excellent results.…”
Section: Splenic Artery Aneurysmsmentioning
confidence: 99%